A Comparative Evaluation of Root Fracture Resistance of Endodontically Treated Teeth Using Two Fiber Posts with Two Ferrule Heights. - Elfallah, Khadiga. (2017)
Abstract: Abstract Purpose The purpose of this project was to evaluate the difference between fracture resistance of the endodontically treated teeth restored with glass fiber posts, and fracture resistance of teeth restored with quartz fiber posts and metal posts with different ferrule heights (1 mm vs. 2 mm). Materials and Methods Sixty extracted human teeth were investigated in the study. Sample criteria included single root teeth; maxillary central incisors, canines, and lower premolars, absence of crown and root decay, cracks, and/or previous endodontic treatment and root length of at least 14 mm. Samples were collected from the Oral and Maxillofacial Surgery Clinic at Tufts University School of Dental Medicine. Samples were disinfected by thymol solution, cleaned and sectioned at 2 mm above the cemento-enamel junction. Root canals were prepared with Gates-Glidden burs. Working length was estimated at 0.5mm short of the apex and all apical seals were preserved about 6 to 7 mm apically. The coronal gutta-percha was removed with the system B heating and then post preparations were established by sequenced sizes of drills until reaching the desired diameter. Post spaces in groups A and C were prepared according to the Parapost system (Coltene /Whaledent Inc, MA) and in group B according to Bisco system (Bisco, Inc, MA). All posts had 10 mm height and 1.5 mm diameter. All posts were cemented with Rely- X -Ultimate cement with acid etch and bonding agent followed by a light cure for 20 Sec per surface. Paracore composite build-up (Coltene /Whaledent Inc, MA) was used for all sixty samples using paraforms (Coltene /Whaledent Inc, MA). All ceramic preparation with deep chamfer finish line of 0.7 MM was performed in all samples with a difference in ferrule height. The hand piece was fixed in a surveyor with angulation of 10° using diamond bur #850c-018. A rubber stop was used in the bur to differentiate the ferrule height for 1mm and 2 mm so that groups (A1-B1-C1) had 1 mm ferrule height while groups (A2-B2-C2) had 2 mm ferrule height. All ceramic crowns of (Empress CAD LT A2/C14) were fabricated using E4D CAD/CAM system by scanning the abutments and milling the crowns then all crowns were cemented with Rely-X-Ultimate cement. The compression test was done by subjecting the specimens to a load while using a universal machine for testing (Instron model 5566A, Norwood, MA) with a crosshead speed 0.5mm/min, load cell of 10K Newton with direction of 135° towards the long axis of a tooth and the mean of maximum compression loads were recorded for each group. The Kruskal-Wallis test was used to compare the three post types twice, once with ferrule height of 1 mm and second with ferrule height of 2 mm. Post-hoc test analyses were conducted via the Mann-Whitney U test with Bonferroni correction (p< 0.05// 3 ≈ 0.017) when the Kruskal-Wallis test was statistically significant. We also used the Mann-Whitney U test for each post type to compare the two ferrule heights. Results This study revealed that the difference in root fracture resistance was statistically significant among the post types (p-value = .021) with 2 mm ferrule. No statistically significant difference was found between the three post types with 1 mm ferrule heights. The metal posts had the highest fracture resistance compared to the quartz posts and the difference was statistically significant (p-value < .005). No statistically significant difference was reported with glass posts comparing with any other post. The difference in ferrule heights within quartz fiber post groups were statistically significant with (p-value < .019) where the 1 mm ferrule group had higher fracture resistance than the 2 mm ferrule group. Conclusion Endodontically treated teeth that have been restored with metal posts had the highest fracture resistance followed by those restored with glass fiber posts and quartz fiber posts. Within quartz fiber posts groups, teeth with ferrule height of 1 mm have an enhanced fracture resistance as compared with those of 2 mm ferrule height and that is explained by the thickness of the remaining dentin structure, which is thicker with 1 mm ferrule groups.; Thesis (M.S.)--Tufts University, 2013.; Submitted to the School of Dental Medicine.; Advisors: Ekaterini Antonellou-Pantekidis,, and Masly Harsono.; Committee: Gerard Kugel, and Matthew Finkelman.; Keyword: Dentistry.